Hematopoietic Stem Cell Transplantation From a Related Donor with Human Leukocyte Antigen 1-Antigen Mismatch in the Graft-Versus-Host Direction Using Low-dose Anti-thymocyte Globulin. (1st December 2020) - Kanda, Junya; Ando, Toshihiko; Kimura, Shun-ichi; Fujiwara, Shin-ichiro; Imada, Kazunori; Fujisawa, Shin; Tachibana, Takayoshi; Atsuta, Yoshiko; Kanda, Yoshinobu
Hematopoietic stem cell transplantation (HSCT) from a related donor with an human leukocyte antigen (HLA) 1-antigen mismatch without in vivo T cell depletion is associated with an elevated risk of severe, acute, and chronic graft-versus-host (GVH) disease (GVHD) and poor survival. Therefore, we conducted a multicenter phase II trial of HSCT using low-dose anti-thymocyte globulin (ATG, thymoglobulin). We recruited patients aged 16–65 years with leukemia, myelodysplastic syndrome, or lymphoma who planned to receive HSCT from a related donor with HLA 1-antigen mismatch in the GVH direction at the HLA-A, -B, or -DR locus. Pretransplantation ATG was administered with standard GVHD prophylaxis consisting of tacrolimus and methotrexate. Thirty-eight patients were eligible for the analysis. The 1-year GVHD-free relapse-free survival (GRFS) was 47%. The 3-year overall survival (OS) was 57%. Age of less than 50 years was associated with better OS. OS in patients with high/very high refined disease risk indexes (rDRIs) was comparable to that in those with low/intermediate rDRIs. The 100-day cumulative incidences of grades II–IV and III–IV acute GVHD were 45% and 18%, respectively. HSCT from a related donor with two allele mismatches showed higher incidences of grades II–IV and III–IV acute GVHD. Three-year cumulative incidences of moderate to severe or severe chronic GVHD were 13% and 3%, respectively. HSCT from a related donor with one locus mismatch at the antigen level using low-dose ATG showed lower incidences of acute and chronic GVHD, which led to acceptable GRFS, OS, relapse, and nonrelapse mortality.